Myth, Social Identification and Commodification (Meta Synthesis On Dreadlocks Research Dieng, Central Java) - Mahmudi, Marwan; Amrullah, Haekal Fajri; Nurhasanah; Surantio, Hadi (Journal of Techno-Social, 2022)
This study departs from 19 research findings with the same subject, namely Dieng dreadlocks discussing the concepts of myth, social identity, and commodification from the perspective or paradigms of each researcher. This is certainly interesting to be meta-synthesized in finding the uniqueness of each of these converged concepts. The general purpose of the research was to find similarities and differences in the findings presented. In particular, the purpose of this study was to explain a comprehensive understanding of myths, social identity, and the commodification of Dieng dreadlocks. The concept presented discussed myth, social identity, commodification. Myth is a series of stories, which may or may not have a basis in origin and may not, which then emerge and last for a long time because they are constantly discussed and remembered in certain societies. Social identity is something that relates to the individual knowledge of certain social groups and to the emotions and judgments caused by members of that group. Commodification is the transformation of use value into exchange value. The research method used was meta-synthesis, namely literature review research where qualitative techniques are used to combine similar primary data to get a new understanding of the issues raised. The use of the meta-synthesis method is to compile findings and to enable the development of new concepts or theories about myths, social identity, and commodification of Dieng dreadlocks. Data were collected using a purposive sampling technique by taking into account quality research results presented in e-journals and institutional/university repositories through the google search engine. The research findings showed that myths and social identities are transformed into commodification when the government includes them on the tourism agenda because rituals that were originally free of economic value have now become of high economic value and become a major tourism asset in the tourism industry in the Dieng Plateau. Keywords: Meta-Synthesis, Myth, Social Identity, Commodification, Dieng Dreads